2008
DOI: 10.1159/000152871
|View full text |Cite
|
Sign up to set email alerts
|

Vegetarian Diet Affects Genes of Oxidative Metabolism and Collagen Synthesis

Abstract: Background/Aim: A vegetarian diet is known to prevent a series of diseases but may influence the balance of carbohydrate and fat metabolism as well as collagen synthesis. This study compares expression patterns of relevant genes in oral mucosa of omnivores and vegetarians. Methods: Quantitative reverse transcriptase polymerase chain reaction was applied for analysis of mRNA levels from carnitine transporter OCTN2, hepatic CPT1A and nonhepatic CPT1B isoforms of carnitine palmitoyltransferase and collagen (CCOL2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…A study by Karlic and colleagues found that a vegetarian diet has a significant impact on genes regulating essential features of carnitine metabolism [113]. Elevated plasma membrane OCTN2 carnitine transporter expression was observed in vegetarians compensating for lower carnitine levels obtained from the diet.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Karlic and colleagues found that a vegetarian diet has a significant impact on genes regulating essential features of carnitine metabolism [113]. Elevated plasma membrane OCTN2 carnitine transporter expression was observed in vegetarians compensating for lower carnitine levels obtained from the diet.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, there seems to be proof that lifestyle factors like physical activity may be more crucial in lowering disease rates than individual dietary habits [20], [28][29]. While, generally speaking, diets based on plants, like vegetarian diets, seem to be associated with a certain health benefit, a lower risk to contract certain chronic diseases [30], and the ability to improve health [31][32], restrictive and monotonous vegetarian diets include the risk of nutritional deficits [2], [18], [19], [30], [33]. Baines et al [9] report that vegetarians take more medication than non-vegetarians.…”
Section: Introductionmentioning
confidence: 99%
“…Research about the dietary habits in Austria is, however, rather sparse and mainly focused on genetic factors [33]–[36]. Therefore, the aim of this study was to investigate health differences between different dietary habit groups among Austrian adults.…”
Section: Introductionmentioning
confidence: 99%
“…Although a large number of studies on vegetarian [24,25,26,27,28,29,30,31,32,33,34,35] and vegan nutrition [20,21,36,37,38,39,40,41] have been published during the last years, only one small study has examined the effect of vegan diets on acid-base homeostasis [42]. Whereas the effect of diets on human acid-base status has significant implications on skeletal health [7,8,9,10,43,44], the primary aim of this cross-sectional study was to investigate how vegan diets affect acid-base balance.…”
Section: Introductionmentioning
confidence: 99%